2021
DOI: 10.1051/e3sconf/202130901028
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Al2O3 in aluminium matrix composites: An overview

Abstract: In this paper, behaviour of Al2O3 in aluminium matrix composites is reviewed for its properties and applications. In addition, many metal matrix composite fabrication processes are also elaborated. In the present days the aluminium metal matrix composite is in high demand because of its superior properties. Its demand is still on rise because of its widespread use in automotive industries, aerospace industries and marine industries. The method of the fabrication of aluminium matrix-based composite is also a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…The tensile and hardness strength have also increased noticeably. Similar outcomes were found by other researchers, 12,37 and it is assumed that the Al grain usually hardens adjacent to the hard particles, weakening the barrier to grain refinement. 3.2.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The tensile and hardness strength have also increased noticeably. Similar outcomes were found by other researchers, 12,37 and it is assumed that the Al grain usually hardens adjacent to the hard particles, weakening the barrier to grain refinement. 3.2.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the increased hardness may be responsible for MMCs’ high compression strength. Singh et al 12 demonstrated that, during the casting stir process, the value of compression strength is greatly increased when we increase the content of alumina reinforcement. Additionally, it has been found that increasing the amount of alumina reinforcement causes a significant increase in the metal matrix’s compressive strength during the casting stir process.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Dispersion-strengthened metal and polymer composites [1], in particular particulatereinforced aluminum matrix composites (PAMCs) [2], are promising structural materials. Their operational properties can significantly exceed the properties of the material used to form the matrix, due to the enhancement of the properties of this material.…”
Section: Introductionmentioning
confidence: 99%